An analysis of the adoption level of modern tea cultivation techniques by the small tea growers (STGs) of Nilgiris district - Bharathwaaj, A; Balasubramaniam, P (Plant Science Today, 2025)
The small tea growers (STGs) of the Nilgiris district play a significant role in Indias’ tea industry, contributing notably to state and national production. Despite advancements in tea cultivation technologies, the adoption rates among these growers remain suboptimal, primarily due to limited access to modern techniques and resources. Tamil Nadu Agricultural University’s Directorate of Open and Distance Learning (DODL) introduced a certificate course in Tea Cultivation Technology to address this gap. This particular study utilizes an Ex-post facto research design. The study was conducted in 2023 and 2024 in the Nilgiris and Coimbatore districts, a major tea-growing tract in Tamil Nadu, India. Using Simple random sampling method, 120 tea growers were selected as the sample size during the survey. A wellstructured pre-tested interview schedule was prepared and the information was collected using personalized interview. Descriptive Statistics, Correlation and Regression analysis followed by Garrett ranking were computed to analyze the adoption level, constraints faced and the suggestions given by the Tea Growers. Based on the findings, this study revealed that most tea growers (49.17%) had a medium level of adoption after enrolling in the certificate course. The most significant challenge was the lack of exposure visits and practical classes (14.72%) followed by inadequate home learning environment. The most ranked suggestion is to enhance the course by increasing hands-on experience sessions and exposure visits (56.66%). Thus, the tea growers consider distance learning a useful educational tool for expanding their knowledge and understanding of agricultural technologies and implementing them at the field level, enabling them to enhance farm conditions and explore business venture opportunities.